Gene electrotransfer with flow-through microchannel and lower alternating voltage generated induced pluripotent cells from human lymphoblastoid cell lines - Miho Ishii-Teshima; Koki Maeda; Kazuki Hanauchi; Emika Asechi; Defan Setyawan; Takeshi Niki; Kenji Nakashima; Hirofumi Kurita; Rika Numano; Takayuki Shibata (PLoS ONE, 2025)
Induced pluripotent stem cells (iPSCs) are useful for studying genetic and rare diseases and can be generated by reprogramming immortalized lymphoblastoid cell lines (LCLs) stored in global repositories with detailed genotype and phenotype data. Traditional bulk-type electroporators are commonly used for gene electrotransfer in reprogramming, but they have major drawbacks, including high costs associated with electric pulse generators and the requirement for fixed volumes for costly reprogramming factors. These limitations hinder cost-effective and scalable iPSC generation, particularly when working with large numbers of LCLs with diverse genotypes. We aimed to develop a flow-through-type electroporator utilizing microchannels for the generation of iPSCs from LCLs, to reduce the costs associated with traditional bulk-type electroporators and enable parallel processing for LCLs with various genotypes. We applied a continuous wave of biphasic alternating voltage (~10 V one-sided amplitude) to micro-scaled electrodes within the microchannel to develop a flow-through electroporator. Numerical simulations were conducted to assess the electric field distribution and its applicability to pore formation in the plasma membrane. To optimize electroporation and flow conditions, we used plasmid pCXLE-EGFP (encoding Green Fluorescent Protein, GFP) for gene electrotransfer to LCLs. Reprogramming factors (pCXLE-hSK, pCXLE-hOCT3/4-shp53-F, pCXLE-hUL) were also delivered to the cells via the same system. The flow-through electroporator achieved 31% transfection efficiency with 78% cell viability, 2 d post-electroporation. In each condition, only 3 µL of cell suspension was used with 10 7 cells/mL of cells and 500 ng/µL plasmid vector. A reprogramming efficiency of 0.048% was obtained, which is comparable to that achieved using bulk-type electroporators. This developed flow-through electroporator with microchannel technology offers significant advantages over traditional methods, including the potential to reduce costs and the ability to process small volumes of cell suspension, making it suitable for parallel processing of LCLs with diverse genotypes. The system provides a promising approach for scalable and potentially cost-effective iPSC generation.